(untitled) (Advances in Applied Mathematics and Mechanics, 2019)
In this paper, we modify the weak Galerkin method introduced in [15] for Stokes equations. The modified method uses the P_k/P_k-1 (k≥1) discontinuous finite element combination for velocity and pressure in the interior of elements. Especially, the numerical traces v_hb which are defined in the interface of the elements belong to the space C^0(E_h), this change leads to less degree of freedom for the resultant linear system. The stability, priori error estimates and L^2 error estimates for velocity are proved in this paper. In addition, we prove that the modified method also yields globally divergence-free velocity approximations and has uniform error estimates with respect to the Reynolds number. Finally, numerical results illustrate the performance of the method, support the theoretical properties of the estimator and show the efficiency of the algorithm.